PENGARUH INFLASI, GDP, DPK, DAN FDR TERHADAP PEMBIAYAAN BERMASALAH PADA BANK JABAR BANTEN SYARIAH - Adelia Sarimukti; Dedi Suselo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Non-Performing Financing is the ratio used to evaluate inadequate Islamic bank funding. The main question in this research is how inflation, gross domestic product (GDP), third-party funding (DPK), and the ratio of Financing to deposits affect Bank Jabar Banten Syariah's non-performing Financing. The sample size for this survey is Bank Jabar Banten Syariah (quarterly) from 2013 to 2020. The Documentation Survey is a data pooling method using the financial details of Bank Jabar Banten Syariah ranging from 2013 to 2020. The research method uses classical hypothesis testing and multiple regression with the SPSS Type 22 process. The conclusion of this study shows that partial inflation and demobilization and reconstruction (FDR) have a negative and insignificant effect on distressed finance, and third-party funds (TPF) have a positive and little impact on distressed finance and gross domestic product (GDP). A significant positive, simultaneous consequence of Inflation, Gross Domestic Product (GDP), Third Party Funds (DPK), and Financing to Deposit Ratio (FDR) on Non-Performing Financing can be noticed from the adjusted R Square score of 0.285 or 28.5% and affected 71.5% remaining on other variables.